Pengaruh Pengembangan Karir, Lingkungan Kerja, dan Kompensasi Terhadap Turnover Intention Karyawan PT. Mahakam Kencana Intan Padi Surabaya - Wahyuniati; Sulastri Irbayuni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of career development, work environment, and compensation on turnover intention among PT employees. Mahakam Kencana Intan Padi Surabaya. The research method used was quantitative with saturated sampling or census techniques, involving all 49 employees. The analysis technique used is the Partial Least Square (PLS) model. The research results show that career development, work environment, and compensation are key factors that can reduce the level of turnover intention at PT. Mahakam Kencana Intan Padi Surabaya.